BIOLOGY AND FISHERY OF THE PALK-BAY SQUID, SEPIOTEUTHIS ARCTIPINNIS GOULD - Rao, K Virabhadra (Indian Journal of Fisheries, 2016)
The only account of the *Palk-Bay Squid, which supports an ancient andlocally well-known minor industry in the Ramnad District of the MadrasState is that of Hornell (1917, 1922) who has described it as 'Loligo sp.' Thewide long fins extending almost the whole length of the mantle, as shownin his figures, indicate that the form dealt with is a member of the genusSepioteuthis and not of Loligo.